Population Genomics of a Cosmopolitan Weed Provides Insights Into Its Local Adaptation and Recent Demographic History - Marilia Souza Lucas; Christoph Rosche; Isabell Hensen; Stefan G. Michalski; Dávid U. Nagy; Diana Gamba; Renske E. Onstein; Karime Abidkulova; Mohammad Al‐Gharaibeh; Ali A. Al‐Namazi; Sirwan Babaei; Fernando Bastida; et al. (Molecular Ecology, 2026)
Invasive plant species present a growing ecological and economic challenge, and often adapt rapidly to their novel environments through complex demographic and evolutionary processes. Invasion genomics offers powerful tools to disentangle these processes, but most studies rely on geographically narrow sampling across native and non‐native ranges. Erigeron canadensis is a cosmopolitan weed native to North America that has successfully invaded diverse climates worldwide. We used double‐digest restriction site‐associated DNA sequencing (ddRADseq) to investigate the genetic diversity and structure of 280 E. canadensis populations across the Northern Hemisphere. We found that native and non‐native populations maintained comparable genetic diversity. Population structure analyses revealed four genetic clusters that were mainly differentiated along latitudinal and aridity gradients. However, one cluster was strongly overrepresented in the non‐native compared to the native range. In the native range, genetic differentiation was shaped by spatial and environmental gradients, while in non‐native regions human‐mediated dispersal and repeated introductions disrupted environmentally driven genetic structure. Migration network analyses revealed limited intercontinental connectivity and a possible role of long‐distance dispersal in within‐range expansions. Genomic offset analyses showed that genotype‐environment mismatches in non‐native populations associated with reduced growth and reproduction. Together, our results indicate that the invasion dynamics of E. canadensis were driven by multiple introductions, population admixture, and lineage sorting, while some genotypes contributed disproportionately to the spread of this invader. The presence of apparent maladaptation suggests that even long‐established invaders may still be evolving in response to their novel environment, raising concerns about potential future expansions.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Analysis of the impact of automaker strategies on lithium price elasticity using a novel bottom-up demand model - Luke Robert Sullivan; Elizabeth A. Moore; Phuong Ho; Alison A. Wang; Gwyneth Margaux Tangog; Karan Bhuwalka; Elsa Olivetti; Richard Roth (Resources, Conservation and Recycling, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Stronger together: a cross-SIG perspective on improving drug development - Luke Fostvedt; Jiawei Zhou; Anna G. Kondic; Ioannis P. Androulakis; Tongli Zhang; Meghan Pryor; Luning Zhuang; Jeroen Elassaiss-Schaap; Phyllis Chan; Helen Moore; Sean N. Avedissian; Jeremy Tigh; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Vertical transport of anthropogenic lead by reversible scavenging in the South Atlantic Ocean - Arianna Olivelli; Maxence Paul; Hui Xu; Katharina Kreissig; Barry J. Coles; Rebekah E.T. Moore; Luke Bridgestock; Micha Rijkenberg; Rob Middag; Maeve C. Lohan; Dominik J. Weiss; Mark Rehkämper; et al. (Earth and Planetary Science Letters, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The use of Beauveria bassiana for the control of the larger grain borer, Prostephanus truncatus, in stored maize: Semi-field trials in Ghana - Belinda Luke; Mavis A. Acheampong; Drauzio E.N. Rangel; Eric W. Cornelius; Stephen K. Asante; Jerry A. Nboyine; Vincent Y. Eziah; Ken O. Fening; Clare Storm; Nick Jessop; Victor A. Clottey; Olivier Potin; et al. (Fungal Biology, 2023)

Comprehensive voxel-wise, tract-based, and network lesion mapping reveals unique architectures of right and left visuospatial neglect - Margaret Jane Moore; Luke Hearne; Nele Demeyere; Jason B. Mattingley (Brain Structure and Function, 2023)
Visuospatial neglect is a common, post-stroke cognitive impairment which is widely considered to be a disconnection syndrome. However, the patterns of disconnectivity associated with visuospatial neglect remain unclear. Here, we had 480 acute stroke survivors [age = 72.8 (SD = 13.3), 44.3% female, 7.5 days post-stroke (SD = 11.3)] undertake routine clinical imaging and standardised visuospatial neglect testing. The data were used to conduct voxel-wise, tract-level, and network-level lesion-mapping analyses aimed at localising the neural correlates of left and right egocentric (body-centred) and allocentric (object-centred) visuospatial neglect. Only minimal anatomical homogeneity was present between the correlates of right and left egocentric neglect across all analysis types. This finding challenges previous work suggesting that right and left visuospatial neglect are anatomically homologous, and instead suggests that egocentric neglect may involve damage to a shared, but hemispherically asymmetric attention network. By contrast, egocentric and allocentric neglect was associated with disconnectivity in a distinct but overlapping set of network edges, with both deficits related to damage across the dorsal and ventral attention networks. Critically, this finding suggests that the distinction between egocentric and allocentric neglect is unlikely to reflect a simple dichotomy between dorsal versus ventral networks dysfunction, as is commonly asserted. Taken together, the current findings provide a fresh perspective on the neural circuitry involved in regulating visuospatial attention, and provide important clues to understanding the cognitive and perceptual processes involved in this common and debilitating neuropsychological syndrome.

The visual fields of the Harpy Eagle (Harpia harpyja) - Anna E. Brewer; Wanderlei de Moraes; Thiago Alegre Coelho Ferreira; Andre Tovares Somma; Zalmir Silvino Cubas; Rogerio R. Lange; Luke P. Tyrrell; Tara M. Czepiel; Esteban Fernández-Juricic; Fabiano Montiani-Ferreira; Bret A. Moore (Journal of Ornithology, 2023)

Foraging guild modulates insectivorous bat responses to habitat loss and insular fragmentation in peninsular Malaysia - Quentin C.K. Hazard; Jérémy S.P. Froidevaux; Natalie Yoh; Jonathan Moore; Juliana Senawi; Luke Gibson; Ana Filipa Palmeirim (Biological Conservation, 2023)

Exposure and behavioral responses of tagged beluga whales ( Delphinapterus leucas ) to ships in the Pacific Arctic - Morgan J. Martin; William D. Halliday; Luke Storrie; John J. Citta; Jackie Dawson; Nigel E. Hussey; Francis Juanes; Lisa L. Loseto; Shannon A. MacPhee; Lisa Moore; Adrian Nicoll; Gregory O'Corry‐Crowe; et al. (Marine Mammal Science, 2023)
Arctic marine mammals face a multitude of challenges linked to climate change, including increasing anthropogenic noise from ship traffic. The beluga whale ( Delphinapterus leucas ), a predominately Arctic endemic cetacean, relies heavily on acoustic communication, with documented overlap between their vocalizations and hearing range and ship noise. Some belugas migrate through areas with the highest levels of ship traffic in the Pacific Arctic and exposure to ship noise is highly probable. Here, we document the responses of nine satellite‐tagged Eastern Beaufort Sea belugas to encounters with ships in the Beaufort, Chukchi, and Bering Seas during July–December 2018. We report 177 occasions when ships were within 125 km of tagged belugas and quantified changes in lateral and vertical movements to investigate individual behavioral responses to ship approaches within 50 km ( n = 23). Belugas' swim speed was negatively correlated with ship distance, showing possible changes in swim speed up to 79 km away. Changes in lateral and vertical movements, indicating disruption of behavior, were observed when some ships passed within 50 km. These findings corroborate previous studies that have shown behavioral responses of belugas to ships at distances far beyond visual range, implying belugas react to low‐amplitude ship noise near ambient levels.

Experimental evidence of size‐selective harvest and environmental stochasticity effects on population demography, fluctuations and non‐linearity - Luke A. Rogers; Zachary Moore; Abby Daigle; Pepijn Luijckx; Martin Krkošek (Ecology Letters, 2023)
Theory and analyses of fisheries data sets indicate that harvesting can alter population structure and destabilise non‐linear processes, which increases population fluctuations. We conducted a factorial experiment on the population dynamics of Daphnia magna in relation to size‐selective harvesting and stochasticity of food supply. Harvesting and stochasticity treatments both increased population fluctuations. Timeseries analysis indicated that fluctuations in control populations were non‐linear, and non‐linearity increased substantially in response to harvesting. Both harvesting and stochasticity induced population juvenescence, but harvesting did so via the depletion of adults, whereas stochasticity increased the abundance of juveniles. A fitted fisheries model indicated that harvesting shifted populations towards higher reproductive rates and larger‐magnitude damped oscillations that amplify demographic noise. These findings provide experimental evidence that harvesting increases the non‐linearity of population fluctuations and that both harvesting and stochasticity increase population variability and juvenescence.

Saturn’s atmospheric response to the large influx of ring material inferred from Cassini INMS measurements - Julianne I. Moses; Zarah L. Brown; Tommi T. Koskinen; Leigh N. Fletcher; Joseph Serigano; Sandrine Guerlet; Luke Moore; J. Hunter Waite; Lotfi Ben-Jaffel; Marina Galand; Joshua M. Chadney; Sarah M. Hörst; et al. (Icarus, 2023)

A multicentre evaluation and expert recommendations of use of the newly developed BioFire Joint Infection polymerase chain reaction panel - Kordo Saeed; Nusreen Ahmad-Saeed; Rachel Annett; Gavin Barlow; Lucinda Barrett; Sara E. Boyd; Nicola Boran; Peter Davies; Harriet Hughes; Gwennan Jones; Laura Leach; Maureen Lynch; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
Septic arthritis is a serious condition with significant morbidity and mortality, routinely diagnosed using culture. The FDA has recently approved the rapid molecular BioFire® Joint Infection Panel (BJIP) for synovial fluid. We aimed to evaluate the BJIP compared to culture and its potential use in patient management. A multicentre retrospective evaluation of BJIP was conducted in the UK and Ireland. Positive percent agreement (PPA) and negative percent agreement (NPA) were calculated between the BJIP and routine culture. A multidisciplinary team (MDT) discussion addressing the optimal or potential case use of the assay practice was facilitated. Three hundred ninety-nine surplus synovial fluid samples (~ 70% from native joints) from eight centres were processed using BJIP in addition to routine culture. An increased yield of positive results was detected using BJIP compared to routine culture (98 vs 83), giving an overall PPA of 91.6% and overall NPA of 93% for the BJIP compared to culture results. The BJIP detected resistant markers and additional organisms that could influence antibiotic choices including Neisseria gonorrhoeae and Kingella kingae . The MDT agreed that the assay could be used, in addition to standard methods, in adult and children patients with specialist advice use based on local needs. Rapid results from BJIP were assessed as having potential clinical impact on patient management. Organisms not included in the panel may be clinically significant and may limit the value of this test for PJI.

Global increase in methane production under future warming of lake bottom waters - Joachim Jansen; Richard Iestyn Woolway; Benjamin M. Kraemer; Clément Albergel; David Bastviken; Gesa A. Weyhenmeyer; Rafael Marcé; Sapna Sharma; Sebastian Sobek; Lars J. Tranvik; Marjorie Perroud; Malgorzata Golub; et al. (Global Change Biology, 2022)
Lakes are significant emitters of methane to the atmosphere, and thus are important components of the global methane budget. Methane is typically produced in lake sediments, with the rate of methane production being strongly temperature dependent. Local and regional studies highlight the risk of increasing methane production under future climate change, but a global estimate is not currently available. Here, we project changes in global lake bottom temperatures and sediment methane production rates from 1901 to 2099. By the end of the 21st century, lake bottom temperatures are projected to increase globally, by an average of 0.86–2.60°C under Representative Concentration Pathways (RCPs) 2.6–8.5, with greater warming projected at lower latitudes. This future warming of bottom waters will likely result in an increase in methane production rates of 13%–40% by the end of the century, with many low‐latitude lakes experiencing an increase of up to 17 times the historical (1970–1999) global average under RCP 8.5. The projected increase in methane production will likely lead to higher emissions from lakes, although the exact magnitude of the emission increase requires more detailed regional studies.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Role of Sea Surface Microlayer Properties in Cloud Formation - Brianna N. Hendrickson; Sarah D. Brooks; Daniel C. O. Thornton; Richard H. Moore; Ewan Crosbie; Luke D. Ziemba; Craig A. Carlson; Nicholas Baetge; Jessica A. Mirrielees; Alyssa N. Alsante (Frontiers in Marine Science, 2021)
To date, the relative contribution of primary marine organic matter to the subset of atmospheric particles that nucleate cloud droplets is highly uncertain. Here, cloud condensation nuclei (CCN) measurements were conducted on aerosolized sea surface microlayer (SML) samples collected from the North Atlantic Ocean during the NASA North Atlantic Aerosols and Marine Ecosystems Study (NAAMES), κ values were predicted for three representative high molecular weight (HMW) organic components of marine aerosol: 6-glucose, humic acid, and ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO). The predicted κ values for pure organic aerosols varied by only ±0.01 across all of the organics chosen. For the desalted SML samples, calculations assuming an organic composition of entirely RuBisCO provided the closest predicted κ values for the desalted SML samples with a mean κ value of 0.53 ± 0.10. These results indicate that it is the sea salt in the SML which drives the cloud formation potential of marine aerosols. While the presence of organic material from the ocean surface waters may increase aerosol mass due to enrichment processes, cloud formation potential of mixed organic/salt primary marine aerosols will be slightly weakened or unchanged compared to sea spray aerosol.

circRNAs expressed in human peripheral blood are associated with human aging phenotypes, cellular senescence and mouse lifespan - Shahnaz Haque; Ryan M. Ames; Karen Moore; Luke C. Pilling; Luanne L. Peters; Stefania Bandinelli; Luigi Ferrucci; Lorna W. Harries (GeroScience, 2020)
Circular RNAs (circRNAs) are an emerging class of non-coding RNA molecules that are thought to regulate gene expression and human disease. Despite the observation that circRNAs are known to accumulate in older organisms and have been reported in cellular senescence, their role in aging remains relatively unexplored. Here, we have assessed circRNA expression in aging human blood and followed up age-associated circRNA in relation to human aging phenotypes, mammalian longevity as measured by mouse median strain lifespan and cellular senescence in four different primary human cell types. We found that circRNAs circDEF6 , c ircEP300 , circFOXO3 and circFNDC3B demonstrate associations with parental longevity or hand grip strength in 306 subjects from the InCHIANTI study of aging, and furthermore, circFOXO3 and circEP300 also demonstrate differential expression in one or more human senescent cell types. Finally, four circRNAs tested showed evidence of conservation in mouse. Expression levels of one of these, circPlekhm1 , was nominally associated with lifespan. These data suggest that circRNA may represent a novel class of regulatory RNA involved in the determination of aging phenotypes, which may show future promise as both biomarkers and future therapeutic targets for age-related disease.

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Development and Implementation of a Continuing Medical Education Program in Canada: Knowledge Translation for Renal Cell Carcinoma (KT4RCC) - Luke T. Lavallée; Ryan Fitzpatrick; Lori A. Wood; Joan Basiuk; Christopher Knee; Sonya Cnossen; Ranjeeta Mallick; Kelsey Witiuk; Marie Vanhuyse; Simon Tanguay; Antonio Finelli; Michael A. S. Jewett; et al. (Journal of Cancer Education, 2019)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

HLA-E, HLA-F, and HLA-G polymorphism: genomic sequence defines haplotype structure and variation spanning the nonclassical class I genes - Chul-Woo Pyo; Luke M. Williams; Yuki Moore; Hironobu Hyodo; Shuying Sue Li; Lue Ping Zhao; Noriko Sageshima; Akiko Ishitani; Daniel E. Geraghty (Immunogenetics, 2006)

Lack of effects of guanfacine on executive and memory functions in healthy male volunteers - Ulrich Müller; Luke Clark; Minh L. Lam; Rebecca M. Moore; C. Louise Murphy; Nicola K. Richmond; Ranbir S. Sandhu; Ingrid A. Wilkins; David K. Menon; Barbara J. Sahakian; Trevor W. Robbins (Psychopharmacology, 2005)